PENGEMBANGAN PENUNTUN PRAKTIKUM KIMIA SESUAI MODEL PEMBELAJARAN PENEMUAN DAN BERBASIS PROYEK - Friska Juliana Purba; Zainuddin Muchtar; Ramlan Silaban (LPPM Universitas Negeri Medan, 2015)
Abstract This research aims to develop practical guidance reaction rates accordingto the model of project-based learning and discovery. To know the differencesignificantly increase learning outcomes that learned by using practical guidancemodel of project-based learning and discovery. Determine the effectiveness of thatlearned how to use the guide practical model of project-based learning anddiscovery. Samples were taken by two classes of experimental class I taught usingpractical guide appropriate experimental models of discovery and class II are taughtusing practical guide appropriate project-based learning model. Before do thisresearch practical guidance has been developed, validated by lecturers and teacherswho are experts in their field and tested to school. Based on the results of thequestionnaire tabulation showed that the average value of project-based learningmodel is higher than the average value of the discovery learning model. Thusobtained that correspond practical guidance based model projects more effectivelyapplied in learning compared with corresponding practical guidance discoverylearning model. Meanwhile, after learning outcomes tested that correspond practicalguide more effective discovery learning model applied in learning compared withcorresponding practical guide project-based learning model. This is evident becausethe students in the experimental class I, which uses practical guide with models ofdiscovery in doing practical implementation to fully follow lab procedures with toolsand materials have also been provided to make the students evenly understand thelab work while in the second experiment class requires students to design ownpractice, as well as determine the tools and materials to find yourself in a group. Theapplication of such a practice models still can not fully be done in schools, becausethe ability of the students have not been evenly distributed so that in practice thereis a group of students who dominate the lab work and the other as observers only. Kata kunci:Development Guidance Practical, DiscoveryModel, Project Based Learning.